(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Bubble deck slab is a method of virtually eliminating all concrete from the middle of a floor slab, which is not performing any structural function, thereby dramatically reducing structural dead weight. High density polyethylene hollow spheres replace the in-effective concrete in the center of the slab, thus decreasing the dead weight and increasing the efficiency of the floor. By introducing the gaps, it leads to 30 to 50 lighter slab which reduces the loads on the columns, walls and foundations, and of course of the entire building. The advantages are less energy consumption - both in production, transport and carrying out, less emission - exhaust gases from production and transport, especially CO2 and reduce the material, the load, lower the cost and it is also a green technology. The aim of this paper is to discuss about the various properties of Bubble deck slab based on various studies done abroad. In the deck technology concrete volume is reduced by replacing it with spherical bubbles, this are locally available which is called as Pepsi balls this balls are made up of high density polyethylene (HDPE).in this experimental program conventional slab and bubble deck slab are cast. This implies the realization of monolithic slab element which will be subjected to two point loading in order to determine the deflection, cracking and failing characteristics. The resultant conclusion will be used in defining failing mechanism.